Poly(vinyl chloride) films incorporated with antioxidant ZnO-flavonoid nanoparticles: a strategy for food preservation - (:unkn) unknown (MDPI, 2024)
Antioxidant films were prepared using poly(vinyl chloride) (PVC) incorporated with 0.5% or 1.0% zinc oxide (ZnO)-flavonoid (quercetin or morin) nanoparticles (NPZnO-Q% or NPZnO-M%) via the casting method. NP incorporation within the polymer matrix influenced the structural, morphological, optical, and thermal properties of the PVC-based films, as well as their antioxidant activity as assessed using the DPPH radical scavenging method. Our results indicated that increasing ZnO-flavonoid NP concentration increased films thickness, while reducing ultraviolet light (UV) transmittance but conserving transparency. The presence of NPZnO-Q% or NPZnO-M% improved the surface uniformity and thermal stability of the active films. In terms of antioxidant activity, there was an enhancement in the DPPH radical scavenging capacity (PVC/ZnO-Q1.0% > PVC/ZnO-Q0.5% > PVC/ZnO-M0.5% > PVC/ZnO-M1.0% > PVC), suggesting that the packaging can help protect food from oxidative processes. Therefore, these antioxidant films represent an innovative strategy for using as active food packaging material, especially intended for aiding in quality preservation and extending the shelf life of fatty foods.
Keywords: Antioxidant films; Active packaging; Zinc oxide nanoparticles; Quercetin; Morin; High-fat food preservation